2020
DOI: 10.2106/jbjs.19.00100
|View full text |Cite
|
Sign up to set email alerts
|

Early Psychological and Social Factors Explain the Recovery Trajectory After Distal Radial Fracture

Abstract: BackgroundThis prospective study identifies the association between demographic, injury, psychological, and social variables, measured early during recovery, with limitations in function (measured by PROMIS UE) at 6-9 months after distal radius fracture. Additionally, we assessed variables associated with PROMIS UE, QuickDASH, PRWE, EQ-5D-3L over time. MethodsA total of 364 adult patients (73% female, median age 65 years , IQR 45.5 -77 years) sustaining an isolated distal radius fracture completed questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 41 publications
4
62
1
Order By: Relevance
“… 11 , 12 After injury and fracture, continued use of opioids is associated along with psychological factors such as greater pain catastrophization, fear of movement, lower self-efficacy, and long-term disability. 12 , 13 For those undergoing surgery, preoperative opioid dependence and fracture complexity are important risk factors for postoperative opioid dependence after fracture fixation, however these are not easily modifiable by treating surgeons. 12 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 After injury and fracture, continued use of opioids is associated along with psychological factors such as greater pain catastrophization, fear of movement, lower self-efficacy, and long-term disability. 12 , 13 For those undergoing surgery, preoperative opioid dependence and fracture complexity are important risk factors for postoperative opioid dependence after fracture fixation, however these are not easily modifiable by treating surgeons. 12 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…37 This suggests that provided a long enough follow-up period, patients undergoing ORIF for a distal radius fracture function similar to the general population, regardless of social deprivation and other biopsychosocial factors that may be impactful in the early recovery phase. 7 We also found that regardless of whether the patients' final radiographic parameters were within the AAOS criteria or not, there was no clinically relevant or statistically significant difference between each group's QuickDASH score. 38 There has been a large amount of research on the radiographic parameters that are the most important to restore after a distal radius fracture.…”
Section: Discussionmentioning
confidence: 55%
“…PROMIS can reliably identify clinical, social, and psychological risk factors for poor outcomes. [25][26][27][28][29][32][33][34][35]. Its weaknesses are lack of specificity for certain body parts, its lack of validation for mental health outcomes, and its ceiling effect in certain active patient populations [23,32,35].…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29][32][33][34][35]. Its weaknesses are lack of specificity for certain body parts, its lack of validation for mental health outcomes, and its ceiling effect in certain active patient populations [23,32,35]. Future research will be directed toward further validation of PROMIS for specific injuries and body regions as well as the incorporation of the mental health profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation